A High‐Power Dielectric Biconical Antenna for Treatment of Subcutaneous Targets. Issue 6 (12th June 2020) - Xiao, Shu; Zou, Xianbing; Huynh, Khiem; Yamada, Ryo; Petrella, Ross; Bani Hani, Maisoun; Beebe, Stephen
Abstract : A dielectric biconical antenna (DiBiCA) for radiating subnanosecond pulses to treat subcutaneous tissue was designed, constructed, and tested. It is composed of a conical wave launcher and truncated conical emitter. In between, there is a short cylinder that provides a space for a ring terminating resistor. The material of the antenna has a dielectric constant of 28, so its size is small (length: 7 cm and aperture diameter: 2.2 cm). It was housed in an oil container to withstand high voltages and avoid surface flashover. The radiated electric field, measured in water, increased as the input voltage increased up to 30 kV but leveled off for higher voltages up to 50 kV, presumably because of losses in the antenna dielectric. The maximum field was 1.5 kV/cm for a depth of 5 mm and 1.0 kV/cm for a depth of 20 mm. Although the dielectric loss mechanism remains to be investigated, the antenna can be useful for noninvasive delivery of subnanosecond pulses to induce biological responses on subcutaneous targets. The DiBiCA radiated pulses were shown to change the viabilities of dendritic cells and macrophages for 10‐min exposure. Bioelectromagnetics. 2020;41:413–424. © 2020 Bioelectromagnetics Society.